Adherence to recombinant human growth hormone therapy in children: influencing factors and clinical implications - Chang, Wenjing; Jin, Hua; Zhou, Qin; Ye, Kan; Dai, Yuee (Frontiers in Pediatrics, 2025)
BackgroundAdherence to recombinant human growth hormone (rhGH) therapy is crucial for achieving optimal outcomes in children with growth disorders. However, non-adherence remains a significant challenge, affecting treatment efficacy and patient prognosis. This study evaluates adherence rates to rhGH therapy in pediatric patients, identifies key influencing factors, and explores strategies to improve adherence.MethodsA retrospective analysis was conducted on 8,621 pediatric patients receiving rhGH therapy in China. Adherence was assessed by the proportion of prescribed doses taken, with good adherence defined as ≥86%. Factors influencing adherence were analyzed using logistic regression models, considering variables such as age, GH formulation type, treatment duration, and regional differences.ResultsThe overall mean adherence rate was 92%, with long-acting GH formulations associated with significantly higher adherence than daily GH injections (94% vs. 91%, p < 0.001). Older children (12–18 years) exhibited better adherence than younger age groups. Patients with severe growth deficits (≤P3 percentile) showed higher adherence than those with moderate deficits. Longer treatment duration was linked to decreased adherence. Regional differences were observed, with patients from Northern Jiangsu demonstrating better adherence than those from Southern Jiangsu.ConclusionAdherence to rhGH therapy is influenced by multiple factors, including GH formulation, age, severity of growth deficit, treatment duration, and regional disparities. Long-acting GH formulations significantly improve adherence. Tailored interventions, such as parental education, digital adherence monitoring, and personalized support programs, are essential to sustain long-term adherence and optimize treatment outcomes.